The Analysis of service quality and price on consumer loyalty through customer satisfaction as a mediating variable during the Covid-19 transition period (case study of 4-stared hotels in Jember) - Syah Riza Octavy Sandy; Feozen Feozen (Jurnal Pariwisata Pesona, 2024)
This research focuses on the Jember Branch of the PHRI (Indonesian Hotel and Restaurant Association) Association as the main reference in formulating hotel marketing strategy policies, both during the transition period of the COVID-19 pandemic and after. Quantitative methods using SPSS 21 were used in this study, with the population consisting of hotel visitors who had stayed at four-star hotels in Jember City. This research began by conducting surveys and testing research instruments. After obtaining valid instruments, surveys are conducted through interviews and questionnaires to collect primary and secondary data. The collected data is then processed using the SPSS statistical application. The next step is to compile a final report based on the results of data analysis, as well as produce scientific publications as an output of this research. The results showed that service quality has a significant influence on customer loyalty and satisfaction. In addition, price also affects customer loyalty and satisfaction at Four Star Hotels in Jember Regency. Customer satisfaction, in turn, affects customer loyalty, as well as mediates the relationship between service quality and price with customer loyalty to Four Star Hotels in Jember Regency.